2004
DOI: 10.1021/jp027546n
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Dynamics of Terminal Acetylenes:  II. Pathway for Vibrational Relaxation in Gas and Solution

Abstract: The pathway for vibrational-energy flow following the excitation of the first excited state of the acetylenic C-H stretch is investigated for a series of 10 terminal acetylenes in room-temperature gases and dilute solutions using transient absorption picosecond infrared spectroscopy. The transient absorption infrared spectra are obtained at three different probe frequencies. These experiments separately detect the population of the excited C-H stretch state, the population of vibrational states with 2 quanta o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 86 publications
(182 reference statements)
1
52
0
1
Order By: Relevance
“…Similarly, Pate and co-workers [55][56][57] showed that solvents ranging from non-polar CCl 4 to highly polar CCl 3 CN do not significantly alter the initial IVR decay rate of the acetylenic C-H stretch (v = 1). The time constants, shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Similarly, Pate and co-workers [55][56][57] showed that solvents ranging from non-polar CCl 4 to highly polar CCl 3 CN do not significantly alter the initial IVR decay rate of the acetylenic C-H stretch (v = 1). The time constants, shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…For example, an extensive treatment of the relaxation following excitation of the fundamental C-H stretch in a series of acetylenic molecules by Yoo et al [15][16][17] shows that some of the molecules have two intramolecular relaxation times in the gas phase although only the fast component survives in solution. They also determine that the fast relaxation comes from strong coupling between the initially excited C-H stretch and a sparse set of states containing two quanta of C-H bend and that the slow relaxation results from weak coupling of these states to the remaining states.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although many studies examine vibrational relaxation in either the gas phase 2-5 or in solution, [6][7][8] only a few experiments directly compare the relaxation dynamics for the isolated and solvated molecule using the same technique. [9][10][11][12][13][14][15][16][17] In this paper we examine the influence that solvation has on IVR and IET by comparing the vibrational relaxation of CH 3 I in various solvents and in the isolated molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the fate of an initially energized molecule requires time resolution on the order of the characteristic few hundred femtosecond encounter time, and modern ultrafast laser technology puts experiments in that regime. The most extensive studies of vibrational dynamics in liquids follow the historical pattern of first assessing energy transfer (25), and there are recent examples (54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69) that particularly address the relaxation of COH stretching excitations. The general picture that emerges from these studies is that in relatively weakly interacting solvents, such as chloroform, the vibrational state structure and couplings of the molecule influence the energy flow within the initially excited molecule most strongly.…”
Section: A Road Ahead: Chemical Reaction Dynamics In Liquidsmentioning
confidence: 99%